Pharmacological Targets of Asundexian Relevant to its Therapeutic Efficacy in Treating Cardiovascular Diseases - Kumar, Arun HS Kumar (Biology, Engineering, Medicine and Science Reports)
Background: Oral anticoagulant which don’t interfere with haemostasis physiology have potential application in management of acute cardiovascular events. Asundexian is once such oral anticoagulant, which is reported to be beneficial by minimising the rate of ischemic events. This study examined the pharmacological basis for cardiovascular benefits of asundexian. Materials and Methods: All potential targets of asundexian in humans were identified by in silco screening in the Swiss Target Prediction server and analysed. Results: Unexpectedly factor XI or XIa was not observed to be targeted by Asundexian in this study. However factor XII and thrombin were observed to be targeted by Asundexian. In addition several GPCR’s, ion channels, enzymes and kinases relevant to positive modulation of cardiovascular physiology were observed to be targeted by Asundexian. Conclusion: The anticoagulant effects of asundexian is likely to be by indirect inhibition of factor XI or XIa by interfering with factor XII and/or thrombin. The cardiovascular benefits of asundexian is likely mediated by broader relevant off target effects.
Keywords: Cardiovascular; Myocardial infarction; Thrombosis; Clot; Anticoagulant